Mujeres Ancestrales - Matecki, Rosana (Venezuela, 2007)
The film tells the story of Christine Roy, a Canadian midwife, who embarks on a journey that starts in Bolivia, meeting fellow Quechua and Aymara midwives. She will find an ancestral knowledge inside the practice of this beautiful task. It is a marvelous trip, a documentary that takes us to the very roots of the oldest most important profession in the world: midwifery.
Verzio Film Festival Submission
Keywords: Documentary films